Analysis of Customs Contributions to North Sumatra Regional Economic Growth - Hidayati Purnama Lubis; Yasmin Miranti (International Forum of Researchers and Lecturers, 2023)
Trade is an activity of exchanging goods and services based on mutual agreement without any element of coercion. Import and export activities are economic activities that cannot be separated from trade and are a unity that can encourage the improvement and growth of the economy in a country. The purpose of this research is to focus on the effect of import-export on economic growth, the evaluation of the contribution of Customs, and the role of international trade supervision. Customs or customs authorities in Indonesia, known as Customs and Excise, are the gateway to international trade. Customs manages state finances and implements state revenue through import duties and excise. The results of this study show that Indonesia's economic growth is influenced by global economic growth. In the first quarter of 2023, export activity weakened with the moderation of international commodity prices which supported the exports of North Sumatra Province. Export performance in North Sumatra grew 2.45% (yoy), lower than the previous quarter which amounted to 9.77% (yoy). Export activities in Indonesia are one of the efforts made by the government to follow the development of industrialization every year. Competition between products in foreign markets depends on price, quality, and quality of goods are important factors in competing in export activities.